Managerial Performance Determinants - Hidayanti Hidayanti; Andry Priharta; Eva Herianti (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The professionalism of the principal has not reached the target with mastery of the principal's competence of 47.1% and this is an important concern for school supervisors. Therefore, this research is important to do. This study aims to examine and analyze total quality management, internal control, organizational commitment, and budget participation on the managerial performance of Vocational High Schools (SMK) in DKI Jakarta. The sample in this study consisted of principals, vice of principals and head of administratives of Vocational High Schools. The number of samples that meet the prerequisites is 99 respondents. The analytical tool used is SEM PLS with SmartPLS 3.0 as a statistical test tool. The results of this study indicate that total quality management affects managerial performance, internal control system affects managerial performance, organizational commitment affects managerial performance, budget participation affects managerial performance. Together, total quality management, internal control, organizational commitment, and budget participation affect managerial performance. This research was conducted during the covid pandemic, so it was limited to meeting managerial parties.